Magnetic Effect on the Optical Energy Gap of ZnGeP2 Single Crystal - Omar, M.S.; Mahmood, F.A.; Saeed, S.R. (Sulaimani Journal for Pure and Applied Sciences, 2002)
The magneto-opticol effect was investigated for the cholcopyrite compound ZnGeP2 ,the change in the energy gap due to the magnetic field was measured to be =~ 0.002 eV at room temperature. The temperature coefficient of AEg.B(T)was found to be 1.67 X10-4 eV/K in lhe temperature range(300-400)K. the reduced effective mass of carriers m* wos calculated and it found to decrease with increasing temperature.
Keywords: ZnGeP2,Magnetooptical effect; Semiconductor compounds; Optical properties